Implementasi Corporate Governance Dan Peningkatan Kinerja Perusahaan - Syamsudin, Syamsudin (Benefit, 2011)
Article describes the benefits of corporate governance, with the implementation of good corporate governance will improve the performance of the company, so the owner will get a return on investment. Good corporate governance will reduce risk, improve profits and firm value